APPLICATION AREAS OF BIOLOGICALLY ACTIVE METABOLITES PRODUCED BY ENDOPHITE BACTERIA - Shodiyeva Dildora; Bobakandova Mekhriniso (Scholar Express Journals, 2023)
Paclitaxel is a chemotherapy drug used to treat several types of cancer, including ovarian cancer, breast cancer, lung cancer, cervical cancer, and pancreatic cancer. But scientists have found the endophyte that synthesizes this substance, Taxomyces andreanea, from a small bushy tree known as Taxus brevifolia, which grows on the Pacific coast of North America. Currently, 19 endophytes have been identified from its composition, and all of them have the ability to synthesize paclitaxel and its analogs. In addition, these studies revealed the ability to synthesize a metabolite known as cichorin A, a metabolite first identified in endophytic microorganisms, which is 10-methoxy 8-methyl3- (prop1-en-2-yl)-3,4-dihydro1H-benzeneisochrom4-ol was found to be. It was named cichorin A because it was first isolated from the root of Cichorium intybus plant. This substance can be used in a wide range of pharmaceutical fields.
Keywords: Paclitaxel; Taxomyces andreanea; Cichorium intybus; mutalism